Inventory of Agroecological Practices as part of the Peasant to Peasant Methodology in Ceará: An instrument to decolonize a territory and (re)value peasant knowledge - Fernandes, Ivanete Ferreira; Barbosa, Lia Pinheiro; Dos Santos Damasceno, Cosma; Rosset, Peter Michael [UNESP] (Universidade Federal do Paraná, 2021)
In this article we address the use of an inventory or mapping of agroecological practices, which is part of the Peasant to Peasant methodology (PtP) for promoting the territorialization of peasant agroecology, as a method that also serves for the epistemic decolonization of a territory. The so-called Green Revolution involved the imposition of exogenous technologies and knowledge, causing the fragmentation and devaluing of local peasant knowledge and farming practices adapted to local conditions. In effect, it was an epistemic colonization. The PtP methodology is based on peasant protagonism to recover and socialize agroecological knowledge. We use the case of the PtP process in the Santana land reform settlement of the Landless Rural Workers Movement (MST) in Ceará, Brazil, to demonstrate and analyze the inventory of Practices as a collective tool for decolonization as part of the territorialization of agroecology.
Inventário de Práticas Agroecológicas na Metodologia de Camponês/a a Camponês/a no Ceará: Um instrumento para descolonizar o território e (re)valorizar o conhecimento camponês
Keywords: Agroecology; Decolonization; Inventory of practices; Peasant to peasant; Territorialization